Physics Learning in Secondary Schools by Sea Water Purification Devices Using Solar Panels: Systematic Literature Review - Ernidawati Ernidawati; Zulia Ulfa; Nur Adh Dhuha; Rayatul Akbar; Mitri Irianti; Zuhdi Ma’aruf; Sri Wilda Albeta; Naila Fauza; Eva Astuti Mulyani; Diah Anugerah Dipuja; Meilan Demolawa (Jurnal Penelitian Pendidikan IPA, 2024)
There are several ways to purify sea water to make it suitable for use, one of which is:is through a purification process by utilizing solar energy. Apart from being cheap, this energy is also renewable and highly available abundant in tropical areas. Solar energy is an important component for Human survival because human life activities are very dependent on energy availability. This research examines solar panel-based sea water purification devices as a physics learning medium in secondary schools. Using the Systematic Literature Review (SLR) method, this research analyzes various studies on the development of sea water purification equipment that utilizes solar panels. This study highlights relevant physical material such as thermodynamics and renewable energy, which is used as a basis for developing sea water purification devices using solar panels. In addition, this research identifies variations in the tools and materials used in the desalination process, as well as the application of these tools in the context of physics learning.